Unikernels: The Rise of the Virtual Library Operating System. - MADHAVAPEDDY, ANIL; SCOTT, DAVID J. (Communications of the ACM, 2014)
The article provides information on the virtual operating systems in cloud computing. Operating-system virtualization in cloud computing allows customers to multiplex virtual machines (VMs) on a shared cluster of physical machines. A VM running on the cloud contains a kernel such as Linux or Windows hosting a primary application running in user space, along with secondary services. It discusses the advantages of the library operating system (liBOS) architecture over more conventional designs, such as allowing applications to access hardware resource directly without making repeated privilege transitions to move data between user space and kernel space.